Pengaruh Media Presentasi dan Komik dalam Pembelajaran Biologi terhadap Hasil Belajar ditinjau dari Motivasi Siswa - Marwatoen, Fatmi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2015)
This research is experimental research which aims to find out: 1) the effect of using presentation media and comics on student biology learning outcomes; 2) the influence of high and low motivation on student biology learning outcomes; 3) the interaction between media usage and motivation towards biology learning outcomes. This study uses Factorial 2 x 2 design, using a population of 123 students consisting of 4 (four) classes held at SMAN 8 Mataram, in the academic year 2012/2013. Data analysis using two-way ANOVA with the help of SPSS 17 for Windows. The results of this study indicate that: 1) there is an influence of media use on student biology learning outcomes (p> 0.05); 2) there is no effect of high and low motivation on student biology learning outcomes (p <0.05); 3) there is no interaction between the use of media and motivation towards biology learning outcomes (p> 0.05).